2013
DOI: 10.2320/matertrans.m2012335
|View full text |Cite
|
Sign up to set email alerts
|

Control of Electrical and Thermal Properties on Sn&ndash;50Zn Alloy by 8 vol%Al<sub>2</sub>O<sub>3</sub> Addition for Pb-Free AC-Low Voltage Fuse Elements

Abstract: The addition of 8 vol%Al 2 O 3 particles in the Sn50Zn was carried out for the control of electrical and thermal properties, for Pb-free fuse elements used in electric power line. The metal matrix composite of the SnZn alloy and Al 2 O 3 particle having the different densities and melting points could be produced by the handling at coexisting range of both liquid and solid phases and showed the homogeneous microstructure of randomly dispersed Al 2 O 3 via ingots. The temperature dependence of specific resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is reported that the microstructural, electrical and thermal properties of Sn50Zn were controlled by addition of 8 vol% Al 2 O 3 with high melting point, high and low values in specific resistivity and thermal diffusivity, respectively. 17) Microstructural characteristics of Sn50Zn as the metal matrix were same to those of Zn50Sn alloy, as described above. In this alloy, the Al 2 O 3 particles were located only in the eutectic region with low melting point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the microstructural, electrical and thermal properties of Sn50Zn were controlled by addition of 8 vol% Al 2 O 3 with high melting point, high and low values in specific resistivity and thermal diffusivity, respectively. 17) Microstructural characteristics of Sn50Zn as the metal matrix were same to those of Zn50Sn alloy, as described above. In this alloy, the Al 2 O 3 particles were located only in the eutectic region with low melting point.…”
Section: Introductionmentioning
confidence: 99%
“…The μ e , , c p and μ measured at 293 and 470 K for both Zn50Sn8 vol%Al 2 O 3 alloys, are listed in Table 1. Their values of Zn50Sn alloy 17) are also listed in this table, as reference. Thermal diffusivity (¡) determined by eq.…”
Section: Comparison In Thermal Diffusivity and Electric Resistivitymentioning
confidence: 99%
“…Therefore, there is the reciprocal relation between melt and un-melt down performance for the fuse elements, and both electrical and thermal properties must be controlled for the practical application. It is reported that the microstructural, electrical and thermal properties of Zn-50mass%Sn were controlled by addition of 8 vol% Al 2 O 3 with high melting point, high and low values in speci c resistivity and thermal diffusivity, respectively 17,18) . Even in the Zn-50Sn-8vol%Al 2 O 3 alloy, the electrical and thermal properties were varied depending on Al 2 O 3 distribution states, or microstructural heterogeneity by the partial melt and solidi cation in the soldering for joining between this alloy and Cu connectors 18) .…”
Section: Introductionmentioning
confidence: 99%